1982
DOI: 10.1111/j.1600-0404.1982.tb03106.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pharmacokinetic observations on sodium valproate - A 5-year follow-up study in 100 children with epilepsy

Abstract: Results of clinical and pharmacokinetic observations on sodium valproate (VPA) are reported from a long-term study in 100 children with epilepsy. VPA is the drug of choice in patients with absences. VPA may preferably be chosen as the first drug in patients with atonic seizures partly because all treatment of these seizures is uncertain, and the effect of VPA may be striking, without side effects. When starting with VPA the great problem of drug interactions is avoided. Treating patients with intractable epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 21 publications
5
51
0
Order By: Relevance
“…The finding that TPM clearance is notably higher in children is not surprising because children have a higher rate of drug metabolism ( 2 ) and their AED dosage requirements may be greater than the requirements in adults (8). It has been observed that concentrations of valproate (VPA) within the therapeutic range are at times not achievable during co-medication, even at dosages exceeding 100 mg/kg/day (9). In addition, children receiving carbamazepine (CBZ) require higher mg/kg dosages than adults, and dosing of phenytoin (PHT) in children can be quite complex and marked by considerable lability (8).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that TPM clearance is notably higher in children is not surprising because children have a higher rate of drug metabolism ( 2 ) and their AED dosage requirements may be greater than the requirements in adults (8). It has been observed that concentrations of valproate (VPA) within the therapeutic range are at times not achievable during co-medication, even at dosages exceeding 100 mg/kg/day (9). In addition, children receiving carbamazepine (CBZ) require higher mg/kg dosages than adults, and dosing of phenytoin (PHT) in children can be quite complex and marked by considerable lability (8).…”
Section: Discussionmentioning
confidence: 99%
“…We superfused slices from naive animals with VPA for up to 25 min and detected no reproducible alterations in the duration or amplitude of evoked oscillations at VPA concentrations of up to 1 mM (Fig. 6 B1-B3), which likely exceeds VPA concentrations resulting from chronic treatment in vivo (Henriksen and Johannessen, 1982). The effects of acute VPA on thalamic oscillations thus appear to be insignificant in our slice preparation.…”
Section: Acute Vpa Treatment Does Not Affect Evoked Oscillationsmentioning
confidence: 99%
“…However, there is little general consensus on the qualitative and quantitative characteristics of these effects. Clinical data suggest that VPA has both immediate and longer-lasting effects: although it effectively treats status epilepticus (Sirven and Waterhouse, 2003), there is poor correlation between plasma levels and clinical efficacy (Burr et al, 1984;Chadwick, 1985;Sundqvist et al, 1998), effective seizure control may only be achieved after days or weeks of treatment (Henriksen and Johannessen, 1982;Bourgeois et al, 1987), and effects may persist after cessation of treatment (Rowan et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…A therapeutic range for VPA in the order of 300 to 600 ìmol/L (40 to 80 ìg/mL) has been suggested for patients with epilepsy, although this range must be regarded as only a rough guide (30,45,49). Similar drug levels are recommended for patients with bipolar disorder (88).…”
Section: Drug Concentrations and Clinical Effectsmentioning
confidence: 99%
“…Its own metabolism may also be stimulated by the enzyme-inducing activity of other AEDs, causing VPA levels to decrease. This is of considerable clinical significance, since it is often difficult to obtain satisfactory efficacy with VPA in patients who are treated also with phenytoin, phenobarbital, primidone, or carbamazepine (30,49).…”
Section: Drug Interactionsmentioning
confidence: 99%